The effect of age on whole brain volume in controls, mild cognitive impairment and Alzheimer’s disease patients: A prospective analysis of MRI data from the ADNI data base. - Dahbour, Said; Abdelrahim, Alaa; Braik, Dina; Alsaid, Aseel; Mustafa, Rawan; Almasri, Yosra; Arar, Saja; AlRyalat, Saif Aldeen (Jordan Medical Journal, 2019)
Background Alzheimer disease (AD) is the most common cause of dementia worldwide. It is characterized by brain atrophy, both on imaging and autopsy, although brain atrophy also occurs during normal aging. In this study, we aim to study brain atrophy during a 2-year interval in AD patients, minimal cognitive impairment (MCI), and normal control (NC).Methods Data were obtained from the Alzheimer’s Disease Neuroimaging Initiative (ADNI). This study included three groups of patients; AD, MCI, and NC. We included participants from ADNI 1, Go, and 2, where patients should have full data regarding demographics, mini-mental state exam (MMSE), and whole brain volume measurements for baseline, 1 year, and 2 years.Results A total of 336 patients included in this study, there were 184 (54.8%) men. In the studied group 65 (19.3%), 150 (44.6%), and 121 (36%) were AD, MCI and NC respectively. The mean change in brain volume for a 1-year interval was 1.52% (±2.15), and for a 2-year interval was 2.22% (±2.12). Only age significantly predicted the 2-year interval change in brain volume (p= 0.009), where one-year increase in age predicted a two-year interval brain volume loss by 0.06% (CI 0.02% to 0.10%) more. Conclusion Among studied factors (age, gender and diagnosis), age was the only factor that significantly predicted the rate of whole brain volume loss with direct correlation between the age and rate of volume loss at 2 years of observation.